The Top 10 Things Executives Should Know About Software. - LIMONCELLI, THOMAS A. (Communications of the ACM, 2019)
The author discusses what business executives need to know about software. He mentions the importance of software to any company, topics such as how software development is incremental, the need to maintain computer security including software, and the need for software developers and operators to work together.